Proverbs, Ecclesiastes, Song of Songs - Murphy, Roland E. (Roland Edmund), 1917-2002; Huwiler, Elizabeth, 1952- (Grand Rapids, Mich. : Baker Books, 2012)
"The authors help the reader understand Hebrew thought expressed in wisdom literature and poetry. Murphy brings greater clarity to Proverbs via literary insight and intrabook connections. Huwiler sets Ecclesiastes in the larger biblical context and is a reliable guide through this consideration of existence and meaning. She also explores the rich imagery of Song of Songs, a celebration of the goodness of human sexuality and love." -- Publisher's description
Originally published: Peabody, Mass. : Hendrickson Publishers ; Cumbria [UK] : Paternoster Press, 1999
Includes bibliographical references and indexes
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries